Analysis of brain functional connectivity in children with autism spectrum disorder and sleep disorders: a fNIRS observational study - Bi, Fengli; Jia, Zhuting; Lv, Lin; Zhang, Yanyan; Zhu, Chuanhua; Wan, Chunxiao (Frontiers in Psychology, 2025)
IntroductionAutism spectrum disorder (ASD) is often associated with sleep disorders, although the neurophysiological reasons behind these issues are poorly understood. In this cross-sectional study, functional near-infrared spectroscopy (fNIRS) was used to compare differences in brain functional connectivity (FC) in children with ASD and sleep disorders and those with ASD that was not complicated by sleep disorders.MethodsA total of 88 children (4–9 years old, either sex) were included in the study. The children were divided into three groups: those with ASD and sleep disorders (ASD with sleep disorder group; n = 29), those with ASD and no sleep disorders (ASD without sleep disorder group; n = 29), and those with typical development (TD group; n = 30). All children with ASD met the diagnostic criteria for the “Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-V).” The ASD group with sleep disorders showed typical sleep disorder symptoms, with a total score of ≥41 on the Children’s Sleep Habits Questionnaire. All children were assessed using the Autism Diagnostic Observation Scale, the Vineland Adaptive Behavior Scale, third edition, the Social Response Scale, and the Children’s Sleep Habits Questionnaire. The fNIRS detection was conducted in a quiet environment.ResultsThe fNIRS data revealed that under resting-state conditions, the supramarginal gyrus [SMG:Cohen’s f = 0.981(L)f = 0.467(R)], inferior frontal gyrus [IFG:Cohen’s f = 0.415(L)f = 0.443(R)], frontopolar area [FPA:Cohen’s f = 0.620(L)f = 0.634(R)], dorsolateral prefrontal cortex [DLPFC:Cohen’s f = 0.593(L)f = 0.547(R)], and visual association cortex [VAC:Cohen’s f = 0.500(L)f = 0.524(R)] of the brain showed lower activity in ASD with sleep disorder group compared with the TD group (p < 0.01). The FC values for the SMG [Cohen’s f = 0.981(L)f = 0.467(R)], RFPA (Cohen’s f = 0.634), DLPFC [Cohen’s f = 0.593(L)f = 0.547(R)], and VAC [Cohen’s f = 0.500(L)f = 0.524(R)] were also lower in the ASD with sleep disorder group than the ASD without sleep disorder group (p < 0.01). The FC values of the LIFG showed a mild negative correlation with social affect scale scores (r = −0.34, p = 0.07), while FC values in the RDLPFC were negatively correlated with restricted repetitive behavior (RRB) (r = −0.41, p = 0.03). The Children’s Sleep Habits Questionnaire scores showed a positive correlation with FC values in the RIFG region of the brain (r = 0.37, p = 0.05).ConclusionThe results indicate that FC in the resting brain of children with ASD complicated with sleep disorders was weaker than that of children with ASD without sleep disorders. Both groups showed weaker FC compared with the TD group. However, due to the limited sample size, the generalizability of the findings requires further validation in multicenter, large-sample studies.